Battle of the Brand Fans: Impact of Brand Attack and Defense on Social Media☆. Issue 1 (August 2018) - Ilhan, Behice Ece; Kübler, Raoul V.; Pauwels, Koen H.
Fans of a brand attack fans of rival brands on social media. Given the nature of such rival brand fan attacks, managers are unsure about how much control they should exercise on brand-negative comments on their owned social media touchpoints, and what brand actions drive these Attack, Defense and Across (ADA) posts. Multimethod analysis identifies ADA's impact across industries of technology, fast food, toothpaste, beverages, and sports apparel. Sentiment analysis identifies that fans posting in both communities stimulate both brand-negative and brand-positive comments. Despite their relatively low prevalence (1–6% of all posts), ADA posts induce broader social-media brand engagement as they substantially increase and prolong the effects of managerial control variables such as communication campaigns and new-product introductions. Brand managers, thus, have specific levers to stimulate the positive consequences of rival brand fan posting on their owned media.